The effects of situational variables on distance covered at various speeds in elite soccer - Lago, C.; Casais, L.; Dominguez. E.; Sampaio, J. (European Journal of Sport Science, 2010)
The aim of this study was to examine the effect of match location, quality of opposition, and match status on distance covered at various speeds in elite soccer. Twenty-seven Spanish Premier League matches played by a professional soccer team were monitored in the 2005-2006 season using a multiple-camera match analysis system. The dependent variables were the distance covered by players at different intensities. Data were analysed using a linear regression analysis with three independent variables: match status (i.e. whether the team was winning, losing or drawing), match location (i.e. playing at home or away), and quality of the opponents (strong or weak). The top-class players performed less high-intensity activity (>19.1 km · h-1) when winning than when they losing, but more distance was covered by walking and jogging when winning. For each minute winning, the distance covered at submaximal or maximal intensities decreased by 1 m (P<0.05) compared with each minute losing. For each minute winning, the distance covered by walking and jogging increased by 2.1 m (P<0.05) compared with each minute losing. The home teams covered a greater distance than away teams during low-intensity activity (<14.1 km · h-1) (P<0.01). Finally, the better the quality of the opponent, the higher the distance covered by walking and jogging. Our findings emphasize the need for match analysts and coaches to consider the independent and interactive effects of match location, quality of opposition, and match status during assessment of the physical component of football performance.